Implementation Of Profit Sharing System In Murabahah Financing At Kspps BMT Nurul Jannah Gresik - Farid Ardyansyah, S.E.,M.M.,CIQnR; Nely Agustin (International Journal of Economics, Business and Innovation Research, 2022)
This study aims to determine the application of the Murabaha financing profit-sharing system at KSPPS BMT Nurul Jannah Gresik. This type of research is qualitative research that uses a descriptive approach, which was carried out at KSPPS BMT Nurul Jannah Gresik. Data collection techniques in this study are interviews, observations, and literature studies. The data analysis used is descriptive, namely by knowing how to apply the profit-sharing system in Murabaha financing at KSPPS BMT Nurul Jannah Gresik. The results of this study show that the profit-sharing calculation system in Murabaha financing at KSPPS BMT Nurul Jannah Gresik applies the Revenue Sharing profit sharing system. The profit-sharing system in KSPPS BMT Nurul Jannah Gresik is by Islamic law with the absence of usury or taking many advantages of this Murabaha financing. KSPPS BMT Nurul Jannah Gresik does not take much advantage instead, KSPPS BMT Nurul Jannah Gresik sets a very low-profit sharing percentage unlike other bank and non-bank financial institutions that set a relatively high-profit sharing and prioritize profits. KSPPS BMT Nurul Jannah Gresik also benefits from corporate financing.